Current Transformational Processes and Prospects for the Development of Intercultural Cooperation in Uzbekistan - Nishonboeva Kunduz Vakhobovna (International Journal on Integrated Education, 2022)
This article highlights the importance of intercultural cooperation in modernizing the culture of Uzbekistan, the role of the cultural heritage of Uzbekistan and its role in the world civilization and further development of national culture based on the concept of further development of national culture in the Republic of Uzbekistan.